Assistance in the Expansion of Neighboring Community Institutions to Accelerate Welfare in Bumiayu Village, Malang City - Putra, Marsudi Dedi; Soleh, Mukhammad; Bagijo, Himawan Estu; Sa'adah, Aghniya Ariza; Ayudita, Nabilah (PT FORMOSA CENDEKIA GLOBAL, 2024)
At the beginning of 2023 in RT 03, Bumiayu Village, Malang City, the number of heads of families reached 198 heads of families (KK). The compulsory expansion from 1 (one) RT to 2 (two) or more RTs is only carried out when the RTs exceed the number of 50 (fifty) households. Therefore, this community service aims to accompany the expansion of the Rukun Neighbor institution to accelerate welfare in RT 03 Bumiayu Village, Malang City. Implementation methods include (1) Focus Group Discussion (FGD), (2) Assistance in the expansion of RT 03 Bumiayu Village Malang City, and (3) Media use from the results of the RT 03 expansion assistance team, Bumiayu Village, Malang City.